2010
DOI: 10.1074/jbc.m110.168229
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms in the Regulation of G Protein-coupled Receptor Trafficking to the Plasma Membrane*

Abstract: ␤ 2 -Adrenergic receptors (␤ 2 -AR) are low abundance, integral membrane proteins that mediate the effects of catecholamines at the cell surface. Whereas the processes governing desensitization of activated ␤ 2 -ARs and their subsequent removal from the cell surface have been characterized in considerable detail, little is known about the mechanisms controlling trafficking of neo-synthesized receptors to the cell surface. Since the discovery of the signal peptide, the targeting of the integral membrane protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…6, A and C). It is known that ␤ 2 receptor expression is controlled at multiple levels, including mRNA translation and protein trafficking (43,44). Thus, one possible explanation for the lack of functional effects of ␤ 2 agonists in activated microglia is the existence of post-translational mechanisms of expression regulation, but their elucidation is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 83%
“…6, A and C). It is known that ␤ 2 receptor expression is controlled at multiple levels, including mRNA translation and protein trafficking (43,44). Thus, one possible explanation for the lack of functional effects of ␤ 2 agonists in activated microglia is the existence of post-translational mechanisms of expression regulation, but their elucidation is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 83%
“…To our knowledge, this is only the second example of a 3′-UTR sequence critically regulating cell surface expression of a GPCR protein. Previously, it has been reported that disruption of the 3′-UTR of the β 2 -adrenergic receptor (β 2 -AR) mRNA interfered with its recognition by the RNA-binding protein HuR, and this in turn led to impaired cell surface expression of β 2 -AR (51, 52). Nuclear binding of HuR to the 3′UTR of β 2 -AR mRNA is thought to prevent translation of the β 2 -AR mRNA while allowing its transit to the cell periphery where unknown mechanisms release the translational block and the locally-translated β 2 -AR protein can efficiently traffic to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear binding of HuR to the 3′UTR of β 2 -AR mRNA is thought to prevent translation of the β 2 -AR mRNA while allowing its transit to the cell periphery where unknown mechanisms release the translational block and the locally-translated β 2 -AR protein can efficiently traffic to the cell surface. Disruption of the 3′ UTR of β 2 -AR mRNA or knockdown of HuR led to premature initiation of translation, resulting in overproduction of β 2 -AR protein in perinuclear polyribosomes but defective trafficking to the cell surface (51). This is reminiscent of the increase in C5aR protein in the GFP-KI +/+ cytosol seen by Western blot and its perinuclear localization on immunofluorescence microscopy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A variable cannot quantum‐tunnel to another state in zero time, so Y will start moving towards its new equilibrium value. In the case of noradrenergic activity, this value will depend on time‐dependent shifts in mRNA transport and translation (Tholanikunnel et al , 2010), as well as protein internalization and recycling (Luttrell & Gesty‐Palmer, 2010; Vayttaden et al , 2010). But then one can argue that what X actually controls is not the equilibrium value of Y , but rather its direction of movement.…”
Section: Time‐independent and Time‐dependent Modelsmentioning
confidence: 99%